2001
DOI: 10.1139/cjz-79-9-1544
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining "gaps" in the distribution of a small carnivore, the common genet (<i>Genetta genetta</i>), in central Spain

Abstract: We studied the pattern of distribution of the common genet (Genetta genetta) in areas in mountains and plains of central Spain, in the middle of the range of the species. We evaluated the role of temperature, rainfall, and habitat features in determining the ecological limits of genet distribution. Genets were very scarce on plateaux and the upper parts of the mountains, but were widely distributed in lower mountain areas. Genets were present in areas with abundant shrub cover, high mean of the mean minimum te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Among these features, high cover and the complexity of the vegetation strata, and organiccontent rich soils seem to be particularly important in determining the occurrence of the species. This result clearly supports the known tendency of genets to occupy areas with dense shrub cover, areas which have greater availability of food, greater abundance of its main prey, the wood mouse, and a lower risk of predation by and competition with other predators (Cugnasse and Riols 1984;Delibes 1988, 1994;Virgo´s and Casanovas 1997;Virgo´s et al 2001). Recent work in southwestern Portugal in cork oak woodland also highlights the importance of high understory cover and old trees for the placement of latrines (Espı´rito-Santo et al 2007).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Among these features, high cover and the complexity of the vegetation strata, and organiccontent rich soils seem to be particularly important in determining the occurrence of the species. This result clearly supports the known tendency of genets to occupy areas with dense shrub cover, areas which have greater availability of food, greater abundance of its main prey, the wood mouse, and a lower risk of predation by and competition with other predators (Cugnasse and Riols 1984;Delibes 1988, 1994;Virgo´s and Casanovas 1997;Virgo´s et al 2001). Recent work in southwestern Portugal in cork oak woodland also highlights the importance of high understory cover and old trees for the placement of latrines (Espı´rito-Santo et al 2007).…”
Section: Discussionsupporting
confidence: 68%
“…The genet has large flexibility in its choice of habitat (Cugnasse and Riols 1984;Calzada 2002), and studies carried out so far have demonstrated an association with high temperature and low rainfall and with woodland and shrubland areas (Palomares and Delibes 1994;Virgo´s and Casanovas 1997;Virgo´s et al 2001;Espı´rito-Santo et al 2007). This species has generalist and opportunistic feeding habits, but in Europe it feeds mainly on small mammals, especially the wood mouse (Apodemus sylvaticus), and on arthropods (Virgo´s et al 1999;Rosalino and Santos-Reis 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several niche axes that could play a role in carnivore coexistence have been analyzed in a variety of ecosystems. Among them, land cover selection and diet preferences are some of the most studied factors (Barrientos & Virgós, 2006;Carvalho & Gomes, 2004; Curveira-Santos, Pedroso, Barros, & Santos-Reis, 2019; Kelly & Holub, 2008;Linkie, Dinata, Nugroho, & Haidir, 2007;Rosalino, Macdonald, & Santos-Reis, 2004;Ruiz-Olmo & López-Martín, 2001;Torre, Arrizabalaga, & Ribas, 2009;Virgós, Romero, & Mangas, 2001).…”
Section: Introductionmentioning
confidence: 99%